2012
DOI: 10.1152/ajpgi.00319.2011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of motor patterns in isolated human colon: are there differences in patients with slow-transit constipation?

Abstract: Spencer NJ, Kyloh M, Wattchow DA, Thomas A, Sia TC, Brookes SJ, Nicholas SJ. Characterization of motor patterns in isolated human colon: are there differences in patients with slow-transit constipation?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 32 publications
5
69
1
Order By: Relevance
“…71,85 However, the delay between CMMCs measured at different points down the empty isolated human colon appears to be considerably shorter than those observed in vivo (Fig. 2B), 71,85 suggesting: (1) because the isolated colons were empty descending inhibition was not effectively activated by colonic content. In fact, CMMCs observed in the isolated human colon appear to propagate in both an oral or anal direction, (2) mucosal release of 5-HT could have been compromised because of hypoxic conditions within the colonic tube because the lumen does not appear to have been perfused and (3) activation of parasympathetic nerves in vivo is necessary for strong activation of IMNs, as it appears to be in the esophagus.…”
Section: Colonic Migrating Motor Complexes In the Isolated Human Colonmentioning
confidence: 86%
See 3 more Smart Citations
“…71,85 However, the delay between CMMCs measured at different points down the empty isolated human colon appears to be considerably shorter than those observed in vivo (Fig. 2B), 71,85 suggesting: (1) because the isolated colons were empty descending inhibition was not effectively activated by colonic content. In fact, CMMCs observed in the isolated human colon appear to propagate in both an oral or anal direction, (2) mucosal release of 5-HT could have been compromised because of hypoxic conditions within the colonic tube because the lumen does not appear to have been perfused and (3) activation of parasympathetic nerves in vivo is necessary for strong activation of IMNs, as it appears to be in the esophagus.…”
Section: Colonic Migrating Motor Complexes In the Isolated Human Colonmentioning
confidence: 86%
“…2C) and are similarly coordinated over long lengths of the large intestine. 71,85 Moreover, intraluminal distension initiates a premature CMMC that is also preceded by a brief relaxation phase, i.e., distension activates descending inhibitory and ascending excitatory nerve pathways. 71,85 However, the delay between CMMCs measured at different points down the empty isolated human colon appears to be considerably shorter than those observed in vivo (Fig.…”
Section: Colonic Migrating Motor Complexes In the Isolated Human Colonmentioning
confidence: 99%
See 2 more Smart Citations
“…Slow myogenic contractions in the human colon can be triggered prematurely by enteric neural stimulation (6). A study of larger specimens of human colon in vitro showed cyclic propagating contractions that could be recorded over large distances and that could also be phase-advanced by enteric nerve stimulation (41). These myogenic events in human colon are clearly influenced by enteric neuronal activity but are not dependent on it.…”
Section: Myogenic Activity and Carbacholmentioning
confidence: 99%